ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER-AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015 - Dimas Nur Setiantoso Putro; Desta Rizky Kusuma (Jurnal Fokus Manajemen Bisnis, 2019)
This study is entitled comparative analysis of financial performance before and after mergers-acquisitions in companies listed on the Indonesia Stock Exchange (IDX) Period 2015. The purpose of this study is to determine differences in financial performance before and after mergers and acquisitions of companies listed on the IDX measured using the ratio Total Asset Turnover, Return On Asset, and Net Profit Margin with Purposive Sampling techniques. This type of data source is secondary data taken from the official website of the Indonesia Stock Exchange (www.idx.co.id). The data taken is the data of financial statements and annual reports and sampling conducted with certain criteria. The population used in this study are companies that have merged and are listed on the Indonesia Stock Exchange, as many as 15 companies. The choice of location or place of research on the Indonesia Stock Exchange (IDX) through the official website www.idx.co.id (2019), the reason for choosing this location is because all data such as financial statements can be trusted. Based on the determined sample criteria from 15 merger-acquisition companies listed on the Indonesian Stock Exchange (IDX), 12 sample companies were obtained that met these criteria. The data analysis method used is descriptive analysis to analyze data by describing or describing the data that has been collected as it is without making conclusions that apply to the public or generalizations. Then the data collected was tested for normality and paired sample t-test with the help of the SPSS 22 application program.